1968
DOI: 10.1063/1.1669896
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Energy Levels of the Trivalent Lanthanide Aquo Ions. IV. Eu3+

Abstract: The free-ion energy level scheme of Eu3+ (aquo) to ∼40 000 cm−1 has been determined from the absorption spectrum of Eu3+ in dilute acid solution at 25°. Energy-level assignments were made on the basis of correlations between calculated and observed intensities. A least-squares fit of 26 J levels, including the effects of configuration interaction, gave an rms deviation of 40 cm−1. The parameter values were E1 = 5573.0, E2 = 26.708, E3 = 557.39, ζ4f = 1326.0, α = 25.336, β = − 580.25, and γ = 1155.7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
383
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(396 citation statements)
references
References 19 publications
11
383
1
1
Order By: Relevance
“…By subtracting both values, an energy difference is obtained which equals the crystal field splitting combined with the total splitting energy of one 4f 6 ( 7 F) term. This can be accurately approximated by using the splitting energy of the 4f 6 ( 7 F) term in Eu 3+ , being 0.62 eV [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By subtracting both values, an energy difference is obtained which equals the crystal field splitting combined with the total splitting energy of one 4f 6 ( 7 F) term. This can be accurately approximated by using the splitting energy of the 4f 6 ( 7 F) term in Eu 3+ , being 0.62 eV [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, cfs (Eu 2+ ,free) is approximated by using the energy level scheme of Eu 3+ . From the degeneracy weighted average of the Eu 3+ 4f 6 ( 7 F J ) multiplets, a value of cfs (Eu 2+ ,free) = 0.39 eV is obtained [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Eu 3+ luminescence peak at 5 D 0 ! 7 F 1 transition is relatively strong, and exhibited no/little change on the surrounding ligand environment due to its MD contribution [35][36][37][38][39][40]. Similarly, the 5 D 0 !…”
Section: Luminescence Spectroscopy and Optical Sensing Of Biomarkermentioning
confidence: 99%
“…The broad excitation band centred at ~260 nm is due to the O-W/Mo charge transfer. The other excitation peaks originate from the intra-configurational 4f-4f transitions of Eu 3+ from the ground state 7 F0 to the excited states 5 D4, 5 L6 and 5 D2 [34]. The main emission line originates from the forced electric dipole transition, 5 D0 -7 F2.…”
Section: Optical Propertiesmentioning
confidence: 99%